Evaluación agronómica del botón de oro (tithonia diversifolia) a diferentes edades en la quinta experimental “El Padmi” de la UNL - Sánchez Rosales, Jhoselyn Arahí (2023)
The agronomic characteristics, forage production and implementation costs of the Golden Button (Tithonia diversifolia) crop were evaluated under edaphoclimatic conditions in the province of Zamora Chinchipe. For this purpose, a crop was implemented in the experimental farm "El Padmi" of the National University of Loja, located in the Los Encuentros parish, Yanzatza canton, Zamora Chinchipe province. After three months of planting, an equalization cut and fertilization with poultry manure was carried out and the data collection and recording of the variables under study began: plant height, number of stems, number of leaves, weight of leaves, weight of stems, leaf/stem ratio, biomass production and dry matter content; at 30, 60 and 90 days; the results were subjected to analysis of variance using a completely randomized design (DCA) and Tukey's test at 0.05 of significance. The results showed a statistical difference for all the agronomic variables between the days, being higher (p≤0.0001) at 90 days of cutting, with values of 4.04 m; 167 #; 437 #;1.09 kg; 2.20 kg and 3.28 kg, respectively. Green forage production varied from 9.3 to 32.8 t/ha/cut; the dry matter content was higher at 90 d of cutting, with 22.05 %; dry matter production was higher at 90 d with 7.2 t/ha/cut. The cost for the implementation of one hectare of Botón de Oro cultivation under the edaphoclimatic conditions of the southern Ecuadorian Amazon was $ 3,210. It is concluded that Tithonia diversifolia adapts very well to the agroecological conditions of the region; and, it can constitute a good alternative to complement the feeding of bovine cattle in the province of Zamora Chinchipe. Keywords: Shrub, cutting age, growth, fodder production, bovine feeding.